Aerial Transportation of Cable-Suspended Loads with an Event Camera - Panetsos, Fotis; Karras, George C.; Kyriakopoulos, Kostas J. (IEEE robotics and automation letters, 2024)
In this work, we investigate the integration of a Dynamic Vision Sensor (DVS) into an Unmanned Aerial Vehicle (UAV) with a cable-suspended load in order to achieve a robust and fast estimation of the cable's state during the transportation of the load. Based on the advantageous properties of event cameras, our ultimate goal is to design a computationally lightweight event processing method that persistently identifies the cable and estimates its complete state - required for any controller with feedback of the cable's state - within a much shorter time period compared to frame-based algorithms. Using a point cloud representation for the incoming event streams, the proposed method achieves the fast detection of the cable while the respective measurements are afterward fitted to a Bézier curve in order to approximate both the cable angle and angular velocity. Our method is initially validated in an indoor environment, where ground truth is available from a motion capture system, and is subsequently deployed in an outdoor one in order to evaluate its robustness against noise. Throughout the outdoor experiment, the feedback provided by the DVS is incorporated into a Nonlinear Model Predictive Control (NMPC) scheme which drives an octorotor towards reference setpoint positions while minimizing the cable angular motion.